Pengaruh Budaya Organisasi terhadap Kinerja Karyawan di KSU Gapoktan Albasiko II Pasaman Barat - Yunisa Rahma; Yossi Eriawati; Fawza Rahmat (Transformasi: Journal of Economics and Business Management, 2024)
This research is motivated by the low level of organisational culture on the performance of employees in KSU GAPOKTAN ALBASIKO II West Pasaman, a picture that organisational culture affects the performance of employees. In this study the researcher connects the problem of lack of awareness and stability of organisational cultural values and still not entirely run by employees, time discipline, innovation, attention to detail, results orientation, team orientation, stability, consistency, honesty, and safety. This study explains whether organisational culture has an effect on employee performance at KSU GAPOKTAN ALBASIKO II. The type of research used is quantitative research which is research with the aim of knowing how much influence the independent variable has on the dependent variable. The research approach used is survey research which is a category of research that aims to analyse the relationships between one variable and another. Primary data was obtained from distributing questionnaires. The population in this study were 53 people and a sample of 53 people. Data analysis and processing techniques using simple linear regression analysis, coefficient of determination (R2), simultaneous test (F test), classical assumption test and hypothesis testing with variables X Organisational Culture and Y Employee Performance. The results showed that there was a significant influence between organisational culture on employee performance.